Formation of the modern areas of the eastern river prawn Macrobrachium nipponense (De Haan) - Kulesh, Victor (Journal of the Belarusian State University. Ecology, 2025)
The formation of the modern range of the alien subtropical species of eastern river shrimp (Macrobrachium nipponense) in new habitats of Asia, Europe and North America has been established from a historical perspective. Vectors of targeted acclimatization of this type of shrimp into cooling ponds of thermal power plants in Belarus, the Russian Federation and Moldova are shown. Data are provided on the accidental introduction of shrimp along with the ballast waters of ships, as well as with commercial fish species that were transported from their natural habitat. Cases of independent penetration of eastern river shrimp into the waters of various continental ecosystems in Europe and Asia are considered. Due to its wide ecological plasticity, the expansion of this eurybiont species will continue into well-warmed estuarine, freshwater and brackish water bodies of the Caspian and Black Seas